Study the relation between luxS gene and forming biofilm and non-forming isolates of Klebsiella pneumonia - Al-Maeni, Mohammad Abdul Rahmman Mohammad; Al-Khazraji, Shaymaa Fouad Rasheed; Hasan, Hussam Mahmood (Iraqi Journal of Science, 2025)
Klebsiella pneumoniae is a notorious pathogenic bacterium, armed with multiple virulence factors, and is commonly associated with pneumonia infections. One of the virulence factors helps K. pneumonia to cause many diseases and escape immune system and antimicrobial effect is biofilm construction. Therefore, the overall aim was to investigate the genic profile for K. pneumonia that formed and non-formed biofilm. The result revealed that around half of the isolates did not form biofilm and this may because luxS gene was present in only two isolates forming biofilm and absent in others while fimH genes were absent in all other isolates. K. pneumonia isolates were sensitive to green tea, Imipenem, and Amikacin antibiotics.  The findings suggest that these compounds may have therapeutic potential against the specific strain of bacterium. Finally, genic variation was identified in the luxS gene between two isolates forming biofilm however, this variation was synonymous and no variation was detected in the amino acid sequence. This may indicate that the luxS gene is highly conserved among K. pneumonia isolates. The absence of luxS and fimH genes in most isolates appears to hinder their ability to form biofilms, making them susceptible to antibiotics such as green tea, Imipenem, and Amikacin.